Thinking and Researching the Ethical Education of the Public Accountant (2019)
This book is a byproduct of the research project Teaching model for the ethical training of public accounting students, conducted by the Universidad Cooperativa de Colombia, the Universidad Augustiniana (Colombia) and the Universidad Pedagógica de Holguín (Cuba). The objective of the project was to show the necessary changes to make the ethics of accounting professionals in Colombia better and better, as well as to expose the principles and codes on which public accounting is based. The first chapter presents advances in the literature review of articles related to the subject in question. The analyzes obtained show two dimensions in the formation of the public accountant: ethical student training and university social responsibility. The second chapter identifies the level of ethical conscience and the interference of the environment in making unethical decisions by students. The third chapter tries to answer the following questions: what research is ongoing to analyze the role of accountant in the ethical domain? What is being said about their responsibility and social ethics? What do authors and universities propose on this topic? The final chapter analyzes what is meant by ‘research’ in the accounting disciplines. Also, think about love in a configurational key and propose to move towards an ethical coexistence: living without expectations.